The application of analytic hierarchy process in higher learning institutions: a literature review - Anis, Azilah; Islam, Rafikul (Inderscience Enterprises, 2015)
In recent years, there has been increasing interest in the application of the Analytic Hierarchy Process (AHP) in the educational sector. However, little effort has been invested in reviewing its application particularly in higher learning institutions (HLIs). As such, this paper attempts to present a thorough literature review of the applications of the AHP in this context. It was observed that 33 articles of AHP application in HLIs were published in the period of 1992-2013. These identified articles were classified according to the publication year, country of origin, integrated techniques that were simultaneously utilised with AHP and also the HLI areas wherein the AHP was applied. The study observed that few articles were published in the period from the 1990’s to the early 2000’s. However, the number of papers has recently increased, especially after 2010, due to recognition of its effectiveness as a decision-making tool in HLIs. The AHP was widely applied in the USA (18 articles) followed by Taiwan, Turkey and India which emerged with three articles each. It is also noted that Quality Function Deployment and Kano model were techniques commonly integrated with AHP by previous researchers. Application of the AHP was dominantly applied in measuring quality education of HLIs (6 articles), faculty member evaluation (6 articles) as well as measuring performance (5 articles). Other areas wherein the AHP was applied include strategic planning, university selection and selection of university majors.